Sports and Health Cluster and Biological Properties in Healthy Nutrition of Athletes - Mamatkulov Ravshanjon Solijonovich (Researchparks Publishing, 2022)
the article defines the scheme of work of a physical culture and health complex. Development of sports and recreational physical activity in Uzbekistan. The organization of regular walking and jogging classes, goals, objectives and advantages are described in detail, since the activities of sports and fitness clusters in Uzbekistan are highly effective, but it is also a matter of improving the physical condition of young generations and students. Younger generation.